Инфузионная терапия: рекомендации на основе здравого смысла - Фесенко, У. А. (PAIN, ANAESTHESIA & INTENSIVE CARE, 2014)
(обзор британского гайдлайна* по инфузионной терапии, адаптированный У.А.Фесенко) * Intravenous fluid therapy in adults in hospital (National Institute for Health and Care Excellence Clinical Guideline, UK. December, 2013) guidance.nice.org.uk/cg174